Mechanoluminescent material for detecting transmission speed of parts as well as preparation method and application of mechanoluminescent material

By combining CaF2:x1%Tm3+, CaF2:x2%Eu3+, CaF2:x3%Tb3+ phosphor with PDMS, it uses RGBML tail length differences to realize visual detection of the transfer speed of the parts, which solves the complex and expensive problems of detection methods in the prior art, and achieves a simple and portable precision detection effect.

CN119552652APending Publication Date: 2025-03-04KUNMING UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411699231.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The prior art is difficult to provide a simple and portable strain rate detection method for detecting the transmission speed of parts, limiting its application in high-precision machinery.

Method used

The high-temperature solid phase method was used to synthesize red, green, and blue (RGB) electroluminescent materials, including CaF2:x1%Tm3+, CaF2:x2%Eu3+, CaF2:x3%Tb3+, and these phosphors were combined with PDMS to prepare into a thin film, and the transmission speed of the parts was visually detected through the difference in ML tail lengths of different colors.

Benefits of technology

It realizes precise detection of component transfer speed, and the inspection results are reliable and practical, avoiding the needs of complex testing systems and high equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119552652A_ABST
    Figure CN119552652A_ABST
Patent Text Reader

Abstract

The invention discloses a mechanoluminescent material for detecting the conveying speed of parts and a preparation method and application of the mechanoluminescent material, and belongs to the technical field of rate detection.The mechanoluminescent material is characterized in that CaF2: x1% Tm < 3 + > fluorescent powder, CaF2: x2% Eu < 3 + > fluorescent powder and CaF2: x3% Tb < 3 + > fluorescent powder are synthesized through a high-temperature solid-phase method; the compounding proportion of the fluorescent powder is regulated based on the service lives of the three different ions; the three kinds of stress luminescence fluorescent powder and PDMS are compounded to prepare a film based on stress luminescence rate detection, so that the film has the stress luminescence property from blue to red under the stress applying condition; due to the different service lives of the emission center, the materials show different ML trailing lengths under the same friction rotating speed; by integrating the RGB ML fluorescent powder into the composite film, the difference of ML trailing lengths of different colors becomes visible, and the difference is increased along with the increase of the rotating speed. Finally, based on the bright color change of ML trailing length at different speeds, the rotation speed visualization of the bearing using the RGB ML film is successfully realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of speed detection, and in particular relates to a mechanoluminescent material for detecting the transmission speed of parts and a preparation method and application thereof. Background Art

[0002] High-precision mechanical parts are very likely to be seriously damaged due to mismatched transmission speeds during the speed change process, which seriously affects the stability of the mechanical structure. Equipment failure warning has become a research hotspot in recent years. At present, photoelectric sensors and high-speed cameras are mainly used to detect the transmission speed of parts. However, complex test systems and high equipment prices limit their application. There is currently no simple and portable strain rate detection method.

[0003] Therefore, there is an urgent need to provide a simple and portable mesoluminescent material and a preparation method thereof for detecting the transmission speed of parts. Summary of the invention

[0004] In view of the above technical problems, the present invention proposes a mechanoluminescent material for detecting the transmission speed of parts and its preparation method and application. It includes: synthesizing red, green and blue (RGB) ML (mechanoluminescent) materials by high temperature solid phase method, including: CaF2: x1% Tm 3+ , CaF2∶x2%Eu 3+ , CaF2∶x3%Tb 3+ , x is the percentage of the amount of the substance; the composite ratio of the phosphors is regulated based on the lifetimes of the three different ions; the three stress-luminescent phosphors are composited with PDMS to prepare a film based on stress-luminescent rate detection; CaF2 has a typical fluorite structure with a face-centered cubic space group of Fm-3m, and rare earth ions (Tm 3+ ,Eu 3+ , Tb 3+ ) replaces Ca 2+ The position of the RGBML phosphors into the lattice; the stress luminescent phosphors do not have stress luminescence properties under grinding conditions; the stress luminescent material has blue to red stress luminescence properties under applied stress conditions; due to the different lifetimes of the emission centers, these materials show different ML tail lengths at the same friction rotation speed; by integrating these RGBML phosphors into the composite film, the differences in ML tail lengths of different colors become visible, and these differences increase with the increase in rotation speed. Finally, based on the vivid color changes of the ML tail lengths at different speeds, the bearing rotation speed visualization using RGBML films was successfully achieved.

[0005] To achieve the above object, the present invention provides the following technical solutions:

[0006] One of the technical solutions of the present invention:

[0007] A mechanoluminescent material for detecting the transmission speed of parts, the raw materials include: PDMS glue and CaF2 as a matrix doped with Tm 3+ , Tb 3+ 、Eu 3+ Three types of stress-luminescent phosphors;

[0008] The chemical formula of the three stress luminescent phosphors is: CaF2: x1% Tm 3+ , CaF2∶x2%Eu 3+ , CaF2∶x3%Tb 3+ ;

[0009] x1=0.05-0.25, x2=3-7, x3=0.1-0.8, the above percentages are molar percentages of CaF2.

[0010] Preferably, the CaF2:x1%Tm 3+ The strongest emission peak is located at 400-500nm, CaF2∶x2%Eu 3+ The strongest emission peak is located at 550-650nm, CaF2∶x3%Tb 3+ The strongest emission peak is located at 500-600nm.

[0011] Preferably, the CaF2:x1%Tm 3+ The luminescence lifetime is 2.1152μs, CaF2∶x2%Eu 3+ The luminescence lifetime is 1.4965ms, CaF2∶x3%Tb 3+ The luminescence lifetime is 2.7205ms.

[0012] Preferably, the stress luminescent phosphor is prepared by a high temperature solid phase method.

[0013] Preferably, the specific preparation process of the high temperature solid phase method is:

[0014] According to the dosage ratio, CaF2 is mixed with thulium oxide, terbium oxide, and europium oxide respectively, and then ground, sintered, and finely ground to obtain CaF2: x1% Tm 3+ , CaF2∶x2%Eu 3+ , CaF2∶x3%Tb 3+ Stress luminescent phosphor.

[0015] Preferably, the grinding time is 0.5-1h;

[0016] The sintering process is: in air conditions, heating to 1100-1200°C at a heating rate of 5°C / min, and then sintering at this temperature for 1h;

[0017] The conditions for the fine grinding are: the fine grinding time is 5-10min.

[0018] Preferably, the PDMS glue is obtained by mixing PDMS (polydimethylsiloxane) A glue and commercially available PDMS B glue (curing agent) at a mass ratio of 10:1. Both are purchased from Dow Corning, and the model is Sylgard 184 silicone lastomer.

[0019] The second technical solution of the present invention:

[0020] The method for preparing the above-mentioned mechanoluminescent material comprises the following steps:

[0021] The three phosphors are mixed with PDMS glue, left to stand in a polytetrafluoroethylene mold, and then dried and demolded to obtain the product.

[0022] Preferably, the mass ratio of each stress-luminescent phosphor to the PDMS glue is 1:(1-4).

[0023] Preferably, the standing process is: at room temperature, the standing time is 5-30 minutes.

[0024] Preferably, the drying conditions are: drying at 60-80° C. for 2-4 hours.

[0025] The third technical solution of the present invention:

[0026] The above-mentioned mesoluminescent material is used in the field of visual detection of component transmission speed.

[0027] Preferably, the step of visually detecting the transmission speed of parts is:

[0028] Attaching the above-mentioned mechanoluminescent material to the inner wall of the acrylic tube;

[0029] The rotation speed of the bearing is measured by adjusting the ML tail color on the surface of the mechanoluminescent material;

[0030] The ML tailing photos of the composite film were recorded using a camera at different loading rates;

[0031] The tone separation technology is used to separate the tones of the original image and extract the blue, red and green ML tail lengths respectively; the visual detection of the rotation speed is achieved by calculating the difference between the ML tail lengths of the three colors.

[0032] Preferably, the tone separation technology adopts Adobe Photoshop 2020 software.

[0033] Compared with the prior art, the present invention has the following advantages and technical effects:

[0034] The present invention combines the advantages of mechanoluminescent materials in the detection of stress states of objects, quantifies the tail lengths of different ion stress luminescence based on the different life decay times, and successfully realizes the real-time detection of the rotation speed of precision parts. The detection results are reliable and practical. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0036] Figure 1 This is a process flow chart of preparing a stress-luminescent composite film according to Example 1 of the present invention;

[0037] Figure 2 The XRD patterns of the three phosphors prepared in Example 1 of the present invention are shown below;

[0038] Figure 3 The excitation and emission spectra of the three phosphors prepared in Example 1 of the present invention;

[0039] Figure 4 The luminescence spectra of the three phosphors after curing in Example 1;

[0040] Figure 5 This is a real stress luminescence picture of the stress luminescence film for rate detection in Example 1;

[0041] Figure 6 is CaF2:x1%Tm in Example 1 3+ Phosphor, CaF2:x2%Eu 3+ Phosphor, CaF2:x3%Tb 3+ Phosphor lifetime decay curve;

[0042] Figure 7 The ML tailing photos of the stress luminescent film recorded by the camera and the ML tailing length pictures of three colors separated by separation technology;

[0043] Figure 8 These are color physical photos of the mechanical luminescence tailing of stress luminescent films at different rotation speeds and mixing ratios. DETAILED DESCRIPTION

[0044] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0045] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0046] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0047] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0048] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0049] A luminescent material for strain rate detection, a red, green, blue (RGB) ML material is synthesized by a high temperature solid phase method, and the raw materials of the luminescent material include: CaF2: x1% Tm 3+ , CaF2∶x2%Eu 3+ , CaF2∶x3%Tb 3+ (x is the percentage of the substance. Among them, rare earth ions replace Ca 2+ position into the lattice), PDMS A glue and cured glue B glue.

[0050] The principle involved is: the present invention regulates the composite ratio of phosphors based on three different ion lifetimes, and composites these three stress luminescent phosphors with PDMS to prepare a film based on stress luminescence rate detection.

[0051] The stress luminescent phosphor does not have stress luminescent properties under grinding conditions; the stress luminescent material has stress luminescent properties from blue to red under stress conditions, CaF2:Tm 3+ The strongest emission peak is located at 400-500nm, CaF2∶Eu3+ The strongest emission peak is located at 550-650nm, CaF2∶Tb 3+ The strongest emission peak is located at 500-600nm.

[0052] By fitting calculation, CaF2∶Tm 3+ The luminescence lifetime is 2.1152μs, CaF2∶Eu 3+ 1.4965ms, CaF2∶Tb 3+ 2.7205ms. Due to the different lifetimes of the emission centers, these materials exhibit different tail lengths at different rotation speeds at the same friction force. When the lifetime of the emission centers is shorter, they transition to the ground state faster, resulting in a shorter fluorescence duration and tail length. On the contrary, when the fluorescence lifetime of the emission centers is longer, they stay in the excited state longer, resulting in a longer duration of luminescence, which leads to a longer tail length.

[0053] By integrating these RGB ML phosphors into composite films, differences in the ML tail lengths of different colors become visible, and these differences increase with increasing rotation speed.

[0054] The present invention also discloses a method for preparing a stress-based luminescent material, comprising the following steps:

[0055] Step 1: Preparation of phosphor based on calcium fluoride doped with rare earth. Calcium fluoride, thulium oxide, terbium oxide and europium oxide are placed in a mortar respectively, and after adding anhydrous ethanol, they are mixed and ground under certain conditions until the anhydrous ethanol is completely volatilized to obtain a mixed raw material; then, under certain conditions, the mixed raw material is sintered, and after sintering and natural cooling, the sintered product is finely ground under certain conditions to obtain a phosphor based on CaF2:x1%Tm 3+ , CaF2∶x2%Eu 3+ , CaF2∶x3%Tb 3+ Phosphor.

[0056] Step 2: Preparation of stress luminescent material based on calcium fluoride phosphor. First, the mass ratio of PDMS glue and curing agent is set to a certain ratio, and the PDMS glue and curing agent are mixed evenly without generating bubbles to obtain a PDMS mixed solution. Then, the phosphor obtained in step 1 is mixed evenly in a certain ratio, and then mixed with the PDMS mixed solution in a certain mass ratio. The mixed solution of phosphor and PDMS is poured into a polytetrafluoroethylene mold. Under certain conditions, the mold is left to stand. Finally, the mold is dried and demolded after drying to obtain a calcium fluoride-based stress luminescent film.

[0057] In some preferred embodiments, in step 1, the mixing and grinding conditions are: the mixing and grinding time is 0.5-1h; the fine grinding conditions are: the fine grinding time is 5-10min;

[0058] The sintering conditions are: under air conditions, the heating rate is 5°C / min, the reaction sintering temperature is 1100-1200°C, and the sintering time is 1h.

[0059] In some preferred embodiments, in step 2, the mass ratio of PDMS to the curing agent is 10:1, and the mass ratio of the phosphor to the PDMS mixed solution is (1:1)-(1:4);

[0060] The standing conditions are: the standing temperature is room temperature, and the standing time is 5-30 minutes;

[0061] The drying conditions are: drying temperature is 60-80℃, and drying time is 2-4h.

[0062] The "room temperature" in the present invention refers to 20-30°C unless otherwise specified.

[0063] The "parts" described in the present invention, unless otherwise specified, refer to parts by mass.

[0064] The raw materials used in the present invention are all purchased from the market.

[0065] The technical solution of the present invention is further illustrated by the following embodiments.

[0066] Example 1

[0067] like Figure 1 As shown, a method for preparing a mechanoluminescent material for detecting the transmission speed of a component is provided, and the specific steps are as follows:

[0068] (1) Commercially available PDMS (polydimethylsiloxane) A glue, commercially available PDMS B glue (curing agent), CaF2: Tm 3+ , CaF2∶Tb 3+ , CaF2∶Eu 3+ The phosphor powders are mixed evenly to form a mixed slurry; wherein the mixed slurry includes 20 parts of commercially available PDMS A glue (main glue), 2 parts of commercially available PDMS B glue (curing agent), CaF2∶Tm 3+ Phosphor 10 parts, CaF2∶Tb 3+ Phosphor 15 parts, CaF2∶Eu 3+ 20 parts of phosphor;

[0069] (2) The phosphors are mixed evenly according to a certain proportion, and then mixed with a PDMS mixed solution (prepared by mixing PDMS A glue (main glue) and commercially available PDMS B glue according to weight proportions). The mixed solution of the phosphors and PDMS is poured into a polytetrafluoroethylene mold, and the mold is allowed to stand for 10 minutes to eliminate bubbles in the mixed solution. Finally, the mold is dried at 70° C. for 2 hours. After drying, the mold is demolded to obtain a calcium fluoride-based stress luminescent film.

[0070] Among them, CaF2∶Tm 3+ The preparation steps of phosphor are as follows:

[0071] 1) mixing calcium fluoride and thulium oxide uniformly to obtain a mixture; the molar amount of thulium oxide is 0.05%, 0.10%, 0.15%, 0.20% and 0.25% of the total molar amount of calcium fluoride respectively;

[0072] 2) The mixture was placed in a protective gas atmosphere, and the temperature was uniformly increased to 1200°C at a heating rate of 5°C / min and subjected to high temperature solid phase reaction for 1 hour, and then cooled to room temperature to obtain CaF2:Tm 3+ Phosphor;

[0073] CaF2∶Tm 3+ The XRD pattern of the phosphor is shown in Figure 2 ,from Figure 2 It can be seen that the XRD of the prepared sample is highly consistent with the standard PDF card (35-0816), indicating that the prepared sample is pure phase;

[0074] After curing, the emission spectrum is shown in Figure 3 ,from Figure 3 It can be seen that the photoluminescence shows blue emission at 400-500nm;

[0075] After curing, the stress luminescence spectrum is shown in Figure 4 ,from Figure 4 It can be seen that the stress luminescence and photoluminescence come from the same luminescence center, and the optimal doping concentration is 0.15%;

[0076] See the actual picture of stress luminescence after the mixed slurry is cured. Figure 5 In (a), it can be seen that the stress luminescence appears as bright blue emission.

[0077] CaF2∶Tb 3+ The preparation method of the phosphor comprises the following specific steps:

[0078] 1) mixing calcium fluoride and terbium oxide uniformly to obtain a mixture; the molar amount of terbium oxide is 0.1%, 0.2%, 0.4%, 0.6% and 0.8% of the total molar amount of calcium fluoride respectively;

[0079] 2) The mixture was placed in a protective gas atmosphere, and the temperature was uniformly increased to 1200°C at a heating rate of 5°C / min and subjected to high temperature solid phase reaction for 1 hour, and then cooled to room temperature to obtain CaF2∶Tb 3+ Phosphor;

[0080] CaF2∶Tb 3+ The XRD pattern of the phosphor is shown in Figure 2 ,from Figure 2 It can be seen that the XRD of the prepared sample is highly consistent with the standard PDF card (35-0816), indicating that the prepared sample is pure phase;

[0081] After curing, the excitation and emission spectra are shown in Figure 3 ,from Figure 3 It can be seen that the photoluminescence shows green emission at 500-600nm;

[0082] After curing, the stress luminescence spectrum is shown in Figure 4 As can be seen from the figure, its stress luminescence and photoluminescence come from the same luminescence center, and the optimal doping concentration is 0.4%.

[0083] See the actual picture of stress luminescence after the mixed slurry is cured. Figure 5 (b) As can be seen from the figure, its stress luminescence manifests as bright green emission.

[0084] CaF2∶Eu 3+ The preparation method of the phosphor comprises the following specific steps:

[0085] 1) mixing calcium fluoride and europium oxide uniformly to obtain a mixture; the molar amount of europium oxide is 3.0%, 4.0%, 5.0%, 6.0% and 7.0% of the total molar amount of calcium fluoride, respectively;

[0086] 2) The mixture was placed in a protective gas atmosphere, and the temperature was uniformly raised to 1200°C at a heating rate of 5°C / min and subjected to high temperature solid phase reaction for 1 hour, and then cooled to room temperature to obtain CaF2∶Eu 3+ Phosphor;

[0087] CaF2∶Eu 3+ The XRD pattern of the phosphor is shown in Figure 2 ,from Figure 2 It can be seen that the XRD of the prepared sample is highly consistent with the standard PDF card (35-0816), indicating that the prepared sample is pure phase;

[0088] After curing, the excitation and emission spectra are shown in Figure 3 ,from Figure 3 It can be seen that the photoluminescence shows red emission at 550-650nm;

[0089] After curing, the stress luminescence spectrum is shown in Figure 4,It can be seen from the figure that its stress luminescence and photoluminescence come from the same luminescence center, and the optimal doping concentration is 5.0%;

[0090] See the actual picture of stress luminescence after the mixed slurry is cured. Figure 5 (c) As can be seen from the figure, its stress luminescence appears as bright red emission.

[0091] In summary, by detecting the difference in the tail length of the multi-color ML film, the visual detection of the rotation speed can be achieved. Therefore, the present application uses the developed ML multi-color film to detect the rotation speed of the bearing.

[0092] Figure 6 is CaF2:Tm in Example 1 3+ Phosphor, CaF2:Eu 3+ Phosphor, CaF2:Tb 3+ The life decay curve of the phosphor; it can be seen from the figure that CaF2∶Tm 3+ The luminescence lifetime is 2.1152μs, CaF2∶Eu 3+ The luminescence lifetime is 1.4965ms, CaF2∶Tb 3+ The luminescence lifetime is 2.7205ms.

[0093] In addition, the present invention also discloses a strain rate visualization detection method based on mechanical luminescence tailing, comprising the following steps:

[0094] The ML multicolor composite film CaF2: 0.15% Tm 3+ / CaF2∶5%Eu 3+ / CaF2∶0.4%Tb 3+ @PDMS is attached to the inner wall of the acrylic tube;

[0095] Use MS-T3001 to simulate the internal structure of the bearing and measure the bearing speed by fine-tuning the ML tailing color on the composite film surface;

[0096] At different loading rates (500r / min, 1000r / min, 1500r / min, 2000r / min, 2500r / min, 3000r / min), the ML tailing photos of the composite film were recorded using a camera ( Figure 7 i);

[0097] Subsequently, Adobe Photoshop 2020 software was used to separate the tones of the original image and extract the blue, red, and green ML tail lengths (e.g. Figure 7 ii, iii and iv);

[0098] By calculating the difference between them, visual detection of the rotation speed is achieved.

[0099] Example 2

[0100] The difference from Example 1 is that in the preparation step (1) of the mechanoluminescent material for detecting the transmission speed of parts, three types of phosphors are replaced by two types, wherein CaF2: 0.15% Tm 3+ and CaF2:0.4%Tb 3+ The weight parts are: 10 parts, 0 parts; 8 parts, 2 parts; 6 parts, 4 parts; 4 parts, 6 parts; 2 parts, 8 parts; 0 parts, 10 parts.

[0101] Figure 8 (a) shows the CaF2:0.15% Tm at different mixing ratios at different speeds. 3+ / CaF2∶0.4%Tb 3+ Physical photos of composite membranes. By changing CaF2∶0.15%Tm 3+ / CaF2∶0.4%Tb 3+ The color of the ML tail shows obvious changes with the mixing ratio. In addition, the length of the ML tail gradually increases with the increase of rotation speed, demonstrating its potential for visual rotation speed detection.

[0102] Example 3

[0103] The difference from Example 1 is that in the preparation step (1) of the mechanoluminescent material for detecting the transmission speed of parts, three types of phosphors are replaced by two types, wherein CaF2: 0.15% Tm 3+ and CaF2:5.0%Eu 3+ The weight parts are: 10 parts, 0 parts; 8 parts, 2 parts; 6 parts, 4 parts; 4 parts, 6 parts; 2 parts, 8 parts; 0 parts, 10 parts.

[0104] Figure 8 (b) shows the CaF2:0.15% Tm at different mixing ratios at different speeds. 3+ / CaF2:5.0%Eu 3+ Physical photos of composite membranes. By changing CaF2∶0.15%Tm 3+ / CaF2:5.0%Eu 3+ The color of the ML tail shows obvious changes with the mixing ratio. In addition, the length of the ML tail gradually increases with the increase of rotation speed, demonstrating its potential for visual rotation speed detection.

[0105] Example 4

[0106] The difference from Example 1 is that in the preparation step (1) of the mechanoluminescent material for detecting the transmission speed of parts, three types of phosphors are replaced with two types, wherein CaF2: 5.0% Eu 3+ and CaF2:0.4%Tb 3+ The weight parts are: 10 parts, 0 parts; 8 parts, 2 parts; 6 parts, 4 parts; 4 parts, 6 parts; 2 parts, 8 parts; 0 parts, 10 parts.

[0107] like Figure 8 (c) shows the CaF2:5.0%Eu at different mixing ratios at different speeds. 3+ / CaF2∶0.4%Tb 3+ Physical photos of composite films. By changing CaF2∶5.0%Eu 3+ / CaF2∶0.4%Tb 3+ The color of the ML tail shows obvious changes with the mixing ratio. In addition, the length of the ML tail gradually increases with the increase of rotation speed, demonstrating its potential for visual rotation speed detection.

[0108] The above are only preferred specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A mechanoluminescent material for detecting the transmission speed of parts, characterized in that: Raw materials include: PDMS glue, CaF2: x1% Tm 3+ Phosphor, CaF: x2% Eu 3+ Phosphor and CaF2:x3%Tb 3+ Phosphor; Among them, x1=0.05-0.25, x2=3-7, x3=0.1-0.

8.

2. The mechanoluminescent material for detecting the transmission speed of parts according to claim 1, characterized in that: The CaF2:x1%Tm 3+ The strongest emission peak is located at 400-500nm, and the luminescence lifetime is 2.1152μs; CaF2∶x2%Eu 3+ The strongest emission peak is located at 550-650nm, and the luminescence lifetime is 1.4965ms; CaF2∶x3%Tb 3+ The strongest emission peak is located at 500-600nm, and the luminescence lifetime is 2.7205ms.

3. The mechanoluminescent material for detecting the transmission speed of parts according to claim 1, characterized in that: The fluorescent powder is prepared by a high-temperature solid phase method.

4. The mechanoluminescent material for detecting the transmission speed of parts according to claim 3, characterized in that: The specific process of the high temperature solid phase method is: According to the percentage, CaF2 is mixed with thulium oxide, terbium oxide, and europium oxide respectively, and then ground, sintered, and finely ground to obtain CaF2: x1%Tm 3+ Phosphor, CaF2: x2% Eu 3+ Phosphor and CaF2:x3%Tb 3+ Phosphor.

5. The mechanoluminescent material for detecting the transmission speed of parts according to claim 4, characterized in that: The sintering process is: Under air conditions, the temperature was increased to 1100-1200°C at a heating rate of 5°C / min, and then sintered at this temperature for 1 h.

6. A method for preparing a mechanoluminescent material for detecting the transmission speed of parts according to any one of claims 1 to 5, characterized in that: The following steps are involved: The fluorescent powder is mixed with PDMS glue, placed in a polytetrafluoroethylene mold, dried, and demolded to obtain the product.

7. The preparation method according to claim 6, characterized in that: The mass ratio of each fluorescent powder to the PDMS glue is 1:(1-4).

8. The preparation method according to claim 6, characterized in that: The standing process is: standing at room temperature for 5-30 minutes; The drying conditions are: drying at 60-80° C. for 2-4 hours.

9. Application of the mechanoluminescent material according to any one of claims 1 to 5 in the field of visual detection of component transmission speed.

10. The use according to claim 9, characterized in that: The method steps for visually detecting the transmission speed of parts are as follows: Attaching the mechanoluminescent material to the inner wall of the acrylic tube; The rotation speed of the bearing is measured by adjusting the ML tail color on the surface of the mechanoluminescent material; The ML tailing photos of the composite film were recorded using a camera at different loading rates; The tone separation technique is used to separate the tones of the original image and extract the blue, red and green ML tail lengths respectively; By calculating the difference between the three color ML tail lengths, visual detection of the rotation speed is achieved.